2023
DOI: 10.1002/cctc.202201436
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nano CdZnS/SnS2/SnO2 Heterojunction for Photocatalytic Degradation of Rhodamine B

Abstract: The accumulation of organic dyes in water and their consequent detrimental effect to ecological environment have attracted worldwide extensive attention. It is urgent to develop rapid and efficient method to degrade organic dyes. In this paper, an efficient CdZnS/SnS 2 /SnO 2 heterojunction is successfully prepared by sequential template approach and hydrothermal method. Comparison with CdZnS and SnS 2 /SnO 2 , the heterogeneous structure of CdZnS/SnS 2 /SnO 2 greatly enhances the photocatalytic degradation ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 69 publications
(107 reference statements)
1
8
0
Order By: Relevance
“…The performance of the photocatalyst has little change after four cycles, and more than 90 % of TCH is removed and the XRD peaks of the photocatalyst are the same. This may be because the photocatalyst is not completely cleaned after the end of the last cycle, and the target remains on its surface, thus reducing the number of active sites and weakening its activity [12,64] . The results of cyclic experiments indicate that the 2MoS 2 /TiO 2 heterojunction is fairly stable during the TCH photocatalytic reaction process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance of the photocatalyst has little change after four cycles, and more than 90 % of TCH is removed and the XRD peaks of the photocatalyst are the same. This may be because the photocatalyst is not completely cleaned after the end of the last cycle, and the target remains on its surface, thus reducing the number of active sites and weakening its activity [12,64] . The results of cyclic experiments indicate that the 2MoS 2 /TiO 2 heterojunction is fairly stable during the TCH photocatalytic reaction process.…”
Section: Resultsmentioning
confidence: 99%
“…[8,9] Therefore, photocatalysis is a promising green and efficient technology for the direct treatment of antibiotics in wastewater. [10][11][12][13] Among all kinds of semiconductors, TiO 2 may be one of the best semiconductor materials to degrade pollutants and decompose water due to its high chemical resistance, low price, and nontoxic. However, TiO 2 can only be activated by ultraviolet light (UV) and has poor activity, which limits its further application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now (2024 January 10th), based on Scopus data there are 337 publications that have reported the use of SnS 2 photocatalyst for wastewater treatment under visible light irradiation and 192 of them are about organic dye removal such as methylene blue, 102–104 methyl orange, 105 and rhodamine B (RhB). 49,106 For heavy metals, hexavalent chromium (Cr( vi )) is the most studied waste water model for photocatalytic investigations of SnS 2 , with 99 publications, which makes SnS 2 one of the most promising materials for Cr( vi ) reduction under visible light irradiation. In the pharmaceutical waste field, tetracycline is the most studied wastewater, with 11 reports showing a good performance for tetracycline removal by a SnS 2 photocatalyst.…”
Section: Sns2 Properties and Photocatalytic Applicationsmentioning
confidence: 99%
“…44 For example, Yu et al 45 first reported the photocatalytic hydrogen production of SnS 2 nanosheets under solar light simulation with H 2 evolution activity of 1.06 mmol h −1 g −1 . In the case of waste water remediation, there are numerous reports for different kinds of waste water such as heavy metals, 46–48 organic dyes, 49,50 and pharmaceutical waste. 51–53 For antibacterial activity, SnS 2 has been applied to inactivate S. aureus and E. coli as reported by Fakhri et al , 40,41 and for air purification SnS 2 has been reported to be able to remove various VOC gasses such as trichloroethylene 54 and formaldehyde 55 as well as NO x gas.…”
Section: Introductionmentioning
confidence: 99%